How can health promotion interventions be adapted for minority ethnic communities? Five principles for guiding the development of behavioural interventions. - Netto, G; Bhopal, Raj; Lederle, N; Khatoon, J; Jackson, A (Oxford University Press, 2010)
The term ‘culturally sensitive’ is often used to describe interventions adapted for minority ethnic communities. However, understanding of strategies for adapting behavioural interventions for such communities is limited. The questions addressed in this paper are: What are the main strategies for adapting interventions to reduce coronary heart disease (CHD) for minority ethnic communities? Why have interventions been adapted in these ways? A systematic review was carried out to investigate interventions for preventing CHD, including promoting physical activity, smoking cessation and healthier diets in Pakistani, Chinese and Indian communities in countries where these groups are minorities. International databases and key websites were searched, and 23 477 titles and abstracts were initially identified. Seventeen papers met inclusion and quality criteria. A ‘meta-ethnographic’ approach to data synthesis was employed to identify underlying principles for adapting interventions. The rationale underpinning adaptations is not made explicit in individual studies, limiting generalizability. Five principles for adapting behavioural interventions for minority ethnic communities were identified: (i) use community resources to publicize the intervention and increase accessibility; (ii) identify and address barriers to access and participation; (iii) develop communication strategies which are sensitive to language use and information requirements; (iv) work with cultural or religious values that either promote or hinder behavioural change; and (v) accommodate varying degrees of cultural identification. While the principles require further testing and verification, they have been generated through a systematic approach to study identification, quality appraisal and data synthesis. This represents significant progress in advancing understanding of adapted behavioural interventions for minority ethnic communities.